Deep Anterior Lamellar Keratoplasty Assisted by a Femtosecond Laser - de Almeida Ferreira, Gabriel [UNESP]; Ghanem, Ramon Coral (Springer Nature, 2022)
Deep anterior lamellar keratoplasty (DALK) is the preferable corneal transplantation technique for anterior corneal diseases in which the endothelium is healthy. However, it is a challenging technique that requires a long learning curve and the use of different methods to separate the anterior stroma from Descemet’s membrane or Dua’s layer. The femtosecond laser (FSL) has earned popularity for penetrating keratoplasty surgery, since it can improve the repeatability and consistency of the shape of the transplant tissue. Research has been made to develop a reliable technique to perform DALK assisted by FSL, since it has the potential to make DALK a more predicable surgery. Unfortunately, the FSL cannot create deep smooth corneal planes, often leading to rough and uneven interfaces, which are optically disadvantageous. Up to date, the most promising strategy is an evolution of the Pachy-bubble technique, in which the embedded optical coherence tomography (OCT) that is present in some FSL platforms is used to obtain real-time intraoperative image of the cornea, making possible to measure it and perform standardized deep tunnels to accomplish the air injection. There are still some drawbacks in the current technique, mostly because the docking system of FSL causes severe corneal applanation, producing significant distortions. This technique has a great potential and future development will hopefully spread this technology and improve patient results.
Keywords: Anterior lamellar keratoplasty; Coherence tomography; Corneal transplantation; Deep anterior lamellar; Eratoplasty; Femtosecond laser; Femtosecond laser-assisted deep; Intraoperative optical; Pachy bubble